Small town settlement Virtual Reality (VR) game - Azidy, Imran Haqeem; Mohammad Ali, Mohammad Mu’izzuddin; Zainal Azmi, Nurazlin; Maarof, Eman Yahya; Kiran, Fatima (IEEE, 2023)
This project focuses on the development of a video game called Small Town Settlement, a city-building game genre for building and managing a self-sustaining settlement for the benefit of society in an entertaining way. This project utilizes the VR technology to create an immersive experience for the players which includes the user interaction and control scheme in the VR, core gameplay mechanics, storyline, character design and level design. The game is developed using Unity on a Windows PC platform. An initial playtesting was conducted on the interaction with objects, interaction with the map, walking around the map, interaction with NPC, interaction with the user interface and menus, and the tutorial of the game; and the feedback received was used to improve one of the features of the game.